Esgoto sanitário e ISSQN: tributação para a sustentabilidade ambiental - Torres, Leonardo Araújo (2012)
With the industrialization process and the constant use of energy to meet the needs of quantitative growth, humans began to produce indiscriminately, without worrying about the reflection of the externalities generated and posted in nature and hence social life of the people, bringing drastic consequences to the habitat of the planet. These consequences were perceived by the scientific community that came to warn the leaders of states on the need to take steps to reverse the process of environmental destruction. In this sense, several actions have been proposed to give a new direction to the development, in the sense that the planet could grow with quality and preserve the environment for future generations, pursuant to art. 225 of the Brazilian Federal Constitution of 1988. Three landmark UN Conferences, Stockholm (1972), ECO/92 (1992), and RIO +20 (2012), outlined goals and principles, as well as draw attention to the global environment. Since then, Brazil has been committed internationally to promote environmental actions preservationists, searching through various actions, reducing the emission of polluting components and destructive of nature and, among the actions taken, is using the indirect taxation to stimulate advocates and discourage destructive nature that use natural resources indiscriminately, generating negative externalities. In this respect, the Constitution of 1988, brings important rules, both environmental nature as tax, allowing us to combine the two materials, making taxation lends itself to environmental sustainability. The definition of tax established in art. 3 of CTN, does not allow the tax revenue is tied to a particular expense, however the use of indirect taxation allows the use taxes to protect the environment. Municipalities are closer to the population, facing its problems, including environmental ones, are forced to implement public policies for environmental protection. Among the kinds of taxes that the municipality may charge the particular is the Tax Services of any kind. Our analysis will be limited to this tribute, as a mechanism for environmental preservation, inducing the collection and treatment of waste from sewage, in municipalities where there is no collection network and treatment, since the municipality may establish different rules, through tax incentives, for example, through exemption, inducing firms to clean pit-treat the waste collected in the service of this nature. Thus, it establishes a financial incentive for people who are willing to protect and reduce the emission of harmful waste to the environment and discourage citizen who insists on not supporting the preservation and reduction of organisms harmful to health and the environment. It follows, then, that taxation is an inducing factor for environmental sustainability and the establishment of an ecological tax under Brazilian municipality is 9 urgent and necessary to stimulate actions regarding the collection and treatment of sewage, as well as reuse their waste. Key-Word: Principles of Environmental Law. ISSQN. Taxation inducing.